Intermediate‐risk differentiated thyroid carcinoma patients who were surgically ablated do not need adjuvant radioiodine therapy: long‐term outcome study. (7th May 2015) - Ballal, Sanjana; Soundararajan, Ramya; Garg, Aayushi; Chopra, Saurav; Bal, Chandrasekhar
Summary: Objective: The mute question is whether patients with DTC of intermediate risk of recurrence, second most common presentation, who were surgically ablated in the first place, ever needed adjuvant RAI therapy? This study exclusively evaluated the long‐term outcome in intermediate‐risk patients with DTC. Design: Two‐arm retrospective cohort study conducted between years 1991 and 2012. Setting: Institutional practice. Patients: Intermediate‐risk DTC patients, with pathologically proven T1/2 N1 M0, T3 with/without N1 M0 disease, with a minimum follow‐up of 12 months, were included. Of 254 patients who fulfilled the inclusion/exclusion criteria, 125 patients were surgically ablated (Gr‐I) and 129 patients had significant remnant and/nodal disease (Gr‐II). No radioiodine in Gr‐I and adjuvant RAI therapy was administered in Gr‐II patients. Measurements: Baseline characteristics were compared and overall survival, event‐free survival, disease‐free survival/overall remission rates and recurrence rates were calculated for both the groups. Results: All baseline patient characteristics were comparable except 24‐h RAIU between two groups. Depending on adjuvant radioiodine therapy outcome, Gr‐II patients were subclassified as Gr‐IIa (ablated) and Gr‐IIb (not ablated). With a median follow‐up duration of 10·3 years (range: 1–21 years), 12/125 (9·6%) patients had disease recurrence and 10 (8%) showed persistent disease in Gr‐I. In Gr‐IIa, 6/102 (5·9%) patients recurred but only one of them was successfully ablated with 131 I, and 5 (4·9%) had persistent disease. However, in Gr‐IIb, 27 patients who failed first‐dose adjuvant RAI therapy, 8/27 (29·6%) showed persistent disease ( P  = 0·000). Overall survival was 100%; however, disease‐free survival rates were 92% and 90%, in Gr‐I and Gr‐II, respectively. Conclusion: Intermediate‐risk surgically ablated patients do not need adjuvant RAI therapy and patients who failed to achieve ablation with first dose of 131 I may be dynamically risk stratified as high‐risk category and managed aggressively.